Investigation of survival and migration potential of differentiated cardiomyocytes transplanted with decellularized heart scaffold. Issue 3 (23rd November 2018) - Akbay, Esin; Onur, Mehmet Ali
Abstract: Mesenchymal stem cell‐derived cardiomyocytes are employed as a source for myocardial cell transplantation as well as for tissue engineering in decellularized tissue scaffolds. The present study aimed at investigating the survival and migration potential of differentiated cardiomyocytes integrated to decellularized scaffolds after implantation into retroperitoneum of rats, and to assess the feasibility of their ectopic use for future cardiovascular tissue engineering. For this purpose, adipose tissue‐derived mesenchymal stem cells (AdMSCs) were first isolated. Cells were labeled by bromodeoxyuridine (BrdU). Decellularized cardiac tissue scaffolds were acquired by application of ionic and non‐ionic detergents and the labeled differentiated cells were seeded onto these tested decellularized scaffolds. After 1, 2, and 4 weeks of implantation, either cell free scaffold (CFS) or cell scaffold (CS) composites were examined by various techniques for ectopic migration potential of the implanted cells and interaction between the seeded cells on scaffolds. Throughout the first and second weeks of implantation, positively stained cells were observed in renal tissue samples. Observations, for cardiomyocytes‐specific gene expression during weeks 1, 2, and 4, showed potential increased over each time period. A reverse transcription polymerase chain reaction (RT‐PCR) results revealed an increased interaction between cells seeded on scaffolds, however CFS test groups showed no significant difference in gene expression. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 561–570, 2019.